Case Report: Clinical analysis of a cluster outbreak of chlamydia psittaci pneumonia - Wu, Yinxia; Xu, Xuemei; Liu, Yun; Jiang, Xiangwei; Wu, Hongjing; Yang, Jie; He, Limei (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To explore the clinical characteristics and prognosis of clustered cases of psittacosis pneumonia. Method We retrospectively analyzed the clinical data of a cluster outbreak of psittacosis pneumonia. The analysis included epidemiological data, clinical symptoms, laboratory results, and prognosis. The diagnosis was made using mNGS and nested PCR technology. Result Of the four cases, two had direct contact with diseased poultry while the other two did not. All cases presented with more than 39.5 °C fever and chills. Additionally, significant increases in C-reactive protein, ferritin, creatine kinase, and lactate dehydrogenase were observed in all cases, while absolute lymphocyte count decreased. Case 2 also had increased calcitonin levels. Acute respiratory failure occurred during the treatment of case 1 and case 2, leading to tracheal intubation and ventilator-assisted ventilation. Unfortunately, case 2 passed away due to sepsis and multiple organ dysfunction, while the other cases had a positive prognosis. Conclusion mNGS facilitated the early diagnosis of psittacosis pneumonia. It is important to note that there is still a substantial risk of human-to-human transmission in psittacosis pneumonia. Absolute lymphocyte count and calcitonin levels can predict the severity and prognosis of the disease.